Current account balance and external adjustment in Turkiye - Hakan Kara; Çağrı Sarıkaya (Koç University-TÜSIAD Economic Research Forum (ERF), 2023)
This paper identifies the cyclical drivers of the current account balance (CAB) in Türkiye and assesses the relevant macro policy implications. We employ the notion of "underlying current account", which corrects for cyclical factors such as global and domestic growth, terms of trade, as well as other exogenous factors including data revisions and idiosyncratic shocks to balance on services. We show that excessive fluctuations in the headline external deficit in recent years can be largely attributed to a combination of unusually large external shocks such as the pandemic and the war, in conjunction with a record-low domestic real interest rates. Special emphasis is put on the role of gold trade and its relation to domestic macro policies. Accounting for the impact of all factors, we estimate that the underlying CAB has shrunk from -6.4% in 2010 to a range of -0.9% to -1.6% in 2023, suggesting a substantial improvement in the external balance during the past decade. However, the underlying balance has significantly deteriorated after 2022, as the jump in inflation coupled with the quasi-fixed exchange rate regime implemented through active use of central bank reserves quickly eroded the competitiveness gains of past years. Besides, as the domestic agents have increased their demand for physical goods/assets to hedge against high inflation under ultra-low real rates, the upward shift in the demand for gold and other imported goods started to feed through the structural component of the CAB. These observations imply that, it may be challenging to lock in the recent gains in the external balance unless the authorities eventually deliver the necessary cyclical adjustment and restore the credibility of the macroeconomic policy framework by re-establishing a nominal anchor.
Keywords: E32; E65; F32; 330; Underlying current account; Turkish economy